2017
DOI: 10.1007/s13197-017-2836-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beta-glucan and resistant starch on wheat dough and prebiotic bread properties

Abstract: White wheat flour is a poor source of dietary fiber. Therefore a demand exists for enrichment of bread with non-digestible prebiotic ingredients that exert health-promoting effects. In this study, the effects of beta-glucan (BG) and resistant starch (RS) on the dough properties and bread-making characteristics were investigated. The water absorption of doughs increased with increasing BG and RS levels. Also, development time and farinograph quality number of BG-enriched doughs remained similar to that of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 39 publications
5
49
1
Order By: Relevance
“…However, the studies carried out do not confirm the positive relationship between the content of β-glucan and the decrease of bread hardness, what was noticed by the predecessors. Mohebbi et al. (2018) also did not confirm this relationship.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…However, the studies carried out do not confirm the positive relationship between the content of β-glucan and the decrease of bread hardness, what was noticed by the predecessors. Mohebbi et al. (2018) also did not confirm this relationship.…”
Section: Resultsmentioning
confidence: 86%
“…Therefore, in samples like oat flour and barley flour, other ingredients were incorporated which could interfere with gluten network and values of G′ and η* were higher than the control sample (Miś et al., 2012). In samples with oat and barley samples, it could occur that β-glucan formed gel, which stabilized the structure of dough as other hydrocolloids (Mohebbi et al., 2018). Moreover, this difference could be as a result of higher molecular weight of β-glucan in oat and barley preparations, which could lead to more comparable viscosity to control sample.…”
Section: Resultsmentioning
confidence: 99%
“…The complexing index of debranched starch–stearic acid complexes reached 89.31% [65], while that of the native starch (yam)–palmitic acid complexes (2%, w / w , starch base) was maximized as 26.39% [66]. In addition to the reduction of the starch glycemic index, high amylose corn starch–lipid complexes inhibited the staling process of baked goods [67], as also evidenced by a recent report, where the firmness of wheat bread during storage was significantly reduced by resistant starch [68].…”
Section: Milk Fats For Bakery Productsmentioning
confidence: 91%
“…Żbikowska et al [31] also reported that replacing 25% of fat with microcrystalline cellulose had the desired effects because the new products were of high sensory quality. Finally, according to Mohebbi et al [40] sensory evaluation showed that the use of prebiotic β-glucan (0.8%-1.2%) has no negative impact on the quality of bread. The amount of fat and the share of β-glucan (BC) in the composition of muffins had an impact on their appearance (external and crumb).…”
Section: Sensory Analysismentioning
confidence: 99%